2019
DOI: 10.1002/oby.22557
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Tissue: Composition, Energy Expenditure, and Energy Content in Adult Humans

Abstract: Objective Chronic positive energy balance leads to obesity, and the “excess” weight is usually described as consisting solely of adipose tissue (AT) or its two components, fat and fat‐free mass (nonfat cell mass, extracellular fluid). This study aimed to clarify the nature of “obesity” tissue. Methods A total of 333 adults had AT, skin, skeletal muscle, bone, heart, liver, kidney, spleen, brain, and residual mass measured or derived using magnetic resonance imaging and dual‐energy x‐ray absorptiometry. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
(65 reference statements)
3
26
0
2
Order By: Relevance
“…Our findings combined with those of Hwaung et al () found the largest proportion increase in taller individuals come from legs. It was hypothesized in Hwaung et al () that these disproportionate increases may be due to lengths of leg bones representing a higher proportion of height in taller individuals. Scaling exponents for leg lengths were larger than 1 for both males and females supporting this conjecture (K and L in Table ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings combined with those of Hwaung et al () found the largest proportion increase in taller individuals come from legs. It was hypothesized in Hwaung et al () that these disproportionate increases may be due to lengths of leg bones representing a higher proportion of height in taller individuals. Scaling exponents for leg lengths were larger than 1 for both males and females supporting this conjecture (K and L in Table ).…”
Section: Discussionsupporting
confidence: 89%
“…Since, thigh circumference scales to the power of ∼0.64 in males and ∼0.68 in females, the scaling exponent of cross‐sectional area will be twice these values; 1.28 in males and 1.35 in females. This calculation provides evidence to support the Hwaung et al () conjecture that taller individuals increase with larger cross‐sectional leg area than compared to their shorter counterparts. This finding is consistent with those found in Bjornerem et al ().…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Second, greater adiposity (i.e., %fat) is also accompanied by enlargement of the SM compartment (12). People who are obese have more SM for their age and height than people who are normal weight (12).…”
Section: Weight and Heightmentioning
confidence: 99%